2022
DOI: 10.1371/journal.pone.0265912
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fabric conditioning products and lint filter pore size on airborne microfiber pollution arising from tumble drying

Abstract: Vented tumble dryers release moist warm air from the drying process to the external environment, usually through pipework linking the appliance to a vent in an exterior wall. Although such dryers contain a lint filter to remove fibers from this air stream, recent reports suggest that this process is incomplete, leading to microfibers being released in the ducted warm air and subsequently polluting the external environment. Microfiber release from wash loads comprising 10 100% cotton and 10 100% polyester T-shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…They detected that 1000 g of cotton textiles can release an average of 42,000 fibres, whereas the PES ones up to 55,330 fibres during 15 min of use, concluding that the PES textiles can produce more microfibres than the cotton ones. In contrast, the results presented by Lant et al, (2022) found that the fibres collected in both lint filter and the mesh adhered to the dryer exhaust were mostly cotton. They highlighted the importance of the pore size of the lint filter, as they discovered that changing from 100 µm to 40 µm reduces up to 35% the release of fibres through the exhaust.…”
Section: Synthetic Textilesmentioning
confidence: 68%
See 3 more Smart Citations
“…They detected that 1000 g of cotton textiles can release an average of 42,000 fibres, whereas the PES ones up to 55,330 fibres during 15 min of use, concluding that the PES textiles can produce more microfibres than the cotton ones. In contrast, the results presented by Lant et al, (2022) found that the fibres collected in both lint filter and the mesh adhered to the dryer exhaust were mostly cotton. They highlighted the importance of the pore size of the lint filter, as they discovered that changing from 100 µm to 40 µm reduces up to 35% the release of fibres through the exhaust.…”
Section: Synthetic Textilesmentioning
confidence: 68%
“…The concerns related to tumble dryers mainly focus on microfibre pollution in air and terrestrial environments, and the consequent human exposure to these airborne microplastics. The drying of clothes is typically done in three ways: 1) Outdoors, by hanging the textiles on a clothesline, 2) Indoors, without any mechanical intervention, using for example drying racks or, 3) Indoors, by using a tumble dryer (Lant et al, 2022). There are three types of tumble dryers: vented tumble dryers, condenser dryers and those with combined washing and drying functions.…”
Section: Synthetic Textilesmentioning
confidence: 99%
See 2 more Smart Citations
“…A 2021 report showed that in the last two decades, global fibre production has increased from 58 million tonnes in 2000 to 109 million tonnes in 2020 (Textile Exchange, 2021). Microfibres are released from clothing during laundering (De Falco et al, 2019Lant et al, 2020), drying (Kapp and Miller, 2020;Lant et al, 2022) and normal wear (De Falco et al, 2020;Sheridan et al, 2020). These eventually end up in the air (Dris et al, 2017), on land (Zubris and Richards, 2005) and in aquatic environments mainly through wastewater treatment plants, run offs and atmospheric deposition (Browne, 2015).…”
Section: Introductionmentioning
confidence: 99%